Case Report: Challenging Otologic Surgery in Patients With 22q11.2 Deletion Syndrome - Verheij, Emmy; Markodimitraki, Laura M.; Stokroos, Robert J.; Thomeer, Hans G. X. M. (Frontiers in Surgery, 2020)
Patients with 22q11.2 deletion syndrome frequently have conductive hearing loss and/or chronic otitis media. Otologic surgery is often opted for. We present two patients undergoing otologic surgery. This case report outlines the typical otologic surgical challenges in patients with 22q11.2 deletion syndrome. Case one is a 52 year old male patient with chronic otitis media who underwent a mastoidectomy. The pre-operative CT scan showed a fused lateral semicircular canal and vestibule. Peroperatively, the lateral semicircular canal could not be used as a landmark to identify the facial nerve. Case two is a 10 year old female patient with conductive hearing loss. A middle ear inspection was performed where a bony epitympanic fixation of the malleus was encountered. In addition, the manubrium of the malleus was atrophic and also fixated. The bony fixation was removed, as was the manubrium of the malleus. Otologists should be aware of these typical anatomical variations in patients with 22q11.2 deletion syndrome. We recommend to use CT scanning of the middle and inner ear when preparing for otologic surgery in 22q11.2 deletion syndrome.